Purification and characterization of a rotenone-insensitive NADH:Q6 oxidoreductase from mitochondria of Saccharomyces cerevisiae - Vries, S. de; Grivell, L.A (European journal of biochemistry, 1988)
A mitochondrial NADH: Q6 oxidoreductase has been isolated from cells of Saccharomyces cerevisiae by a simple method involving extraction of the enzyme from the mitochondrial membrane with Triton X‐100, followed by chromatography on DEAE‐cellulose and blue Sepharose CL‐6B. By this procedure a 2000‐fold purification is achieved with respect to whole cells or a 150‐fold purification with respect to the mitochondrion. The purified NADH dehydrogenase consists of a single subunit with molecular mass of 53 kDa as indicated by SDS/poly‐acrylamide gel electrophoresis. The enzyme contains FAD, non‐covalently linked, as the sole prosthetic group with Em,7.67.6 = ‐370 mV and no iron‐sulphur clusters. The enzyme is specific for NADH with apparent Km= 31 μM and was found to be inhibited by flavone (I50= 95 mUM), but not by rotenone or piericidin. The purified enzyme can use ubiquinone‐2, ‐6 or ‐10, menaquinone, dichloroindophenol or ferricyanide as electron acceptors, but at different rates. The greatest turnover of NADH was obtained with ubiquinone‐2 as acceptor (2500 s−1). With the natural ubiquinone‐6 this value was 500s‐1. The NADH:Q2 oxidoreductase activity shows a maximum at pH 6.2, the NADH:Q6 oxidoreductase activity is constant between pH 4.5‐9.0. The amount of enzyme in the cell is subject to glucose repression: it increases slightly when cells, grown on glucose or lactate, enter the stationary phase. The experiments performed so far suggest that the enzyme purified in this study is the external NADH:Q6 oxidoreductase, bound to the mitochondrial inner membrane and that it is involved in the oxidation of cytosolic NADH. The relation of this enzyme with respect to various other NADH dehydrogenases from yeast and plant mitochondria is discussed.